An Application on Women Safety Using Embedded Systems and IoT - et al., K Hari Kishore (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As far as women safety is concerned. Especially in our country the standards are going on decreasing day by day. According to National Crime Records Bureau (NCRB) the incidents of kidnapping and abductions rose to 64 per million to 74 per million which is devastating. If it goes on increasing like this, In the coming years there will be a tremendous rise in crime rate especially against women. It is our responsibility to protect our mothers, sisters, friends and each and every woman in our family. There are many devices in the market for this application that is sending locations and alert messages to the family of the user. But, all the devices need the response from the user when they are in danger to send the alert messages or such to their family or emergency services. But there might be situations where the user has zero chances to respond or send any alert messages to their family. We came up with a solution where the alert messages and current location of the user are sent automatically to their family when they are in danger without any response from the user. We achieved it using the pulse rate sensor PPG (Photoplethysmography sensor) using which we measured the abnormal rise in heart rate when the user is in danger. This paper deals with the functionality and implementation of our idea in Embedded Systems and IoT.